Improving Access to New Treatments with Value Based Pricing: An Indian Perspective - Amit Dang; Shilpa Mendon; Pruthvi Desireddy (Pharmacology, Toxicology and Biomedical Reports, 2016)
The last few years have witnessed significant changes in pharmaceutical pricing model across the world. These changes were driven primarily by payers in an attempt to control rising health care costs. As per the old concept of pharmaceutical pricing model, prices were determined by market forces with hardly any scrutiny by regulatory bodies. These old methods have given way to some of the newer concept such as the Value Based Pricing (VBP), Health Technology Assessment (HTA) and Health Outcomes Analysis (HOA). VBP is an innovative method of pricing medicines wherein both the payers and pharma companies agree to link payment for a medicine to value achieved i.e. actual observed in real-world performance. Pricing is based on willingness to pay or the perceived additional benefit of new drugs relative to established comparator therapies. Value based pricing results in improved patient outcomes and ensures consistent access to medicines. As a result, elements of VBP are commonly embraced in mature pharmaceutical markets viz. Australia, Belgium, Canada, Denmark, France, Germany, Italy, Japan, the Netherlands, Norway, South Korea, Spain, Sweden and the United Kingdom (beginning autumn 2014). However, regulators in India are lagging behind other countries in adopting elements of VBP in their pricing model. This review will discuss various aspects of VBP including its impact on health care system and patients; barriers to the use of VBP; and reasons for its absence in India.
Keywords: Health Outcomes; Health Technology Assessment; Pharmaceutical Pricing.; Treatment Access; Value Based Pricing